A Minimal Physiologically Based Model of the HPA Axis under Influence of the Sleep-Wake Cycles - Postnova, S.; Fulcher, R.; Braun, H. A.; Robinson, P. A. (Pharmacopsychiatry, 2013)
The hypothalamic-pituitary-adrenal axis (also called the HPA or stress axis) exhibits distinct circadian and ultradian rhythms in cortisol release that cannot be explained solely by the feedback loops from cortisol to the control systems in the paraventricular nucleus (PVN) and pituitary gland. The HPA axis is intimately connected with other brain functions. In particular, it is strongly affected by the sleep-wake cycles via direct and indirect effects of the circadian and homeostatic mechanisms. For example, the HPA axis has direct inputs from the master circadian clock in the suprachiasmatic nuclei (SCN), and from the various sleep-wake related neuronal populations, which themselves are under the effects of the circadian and homeostatic processes. In this paper a first step towards a physiologically based mathematical model of the HPA-axis under effects of the sleep-wake cycles is presented. This model accounts for 3 major characteristics of daily cortisol profile in the blood: i) abrupt increase of cortisol concentration in response to awakening, the so-called cortisol-awakening response (CAR); ii) reduced cortisol levels during daytime with underlying ultradian oscillations; and iii) suppression of cortisol release during sleep.
Keywords: cortisol; ACTH; CRH; sleep; circadian; homeostatic; cortisol-awakening-response; hippocampus